CLINICAL AND IMMUNOLOGICAL CHARACTERISTICS OF VIRAL HEPATITIS B AND C IN ADOLESCENTS - Shodmonov Iskandar Sergeevich (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Relevance of the topic. Viral liver lesions are still one of the pressing medical and social problems of modern hepatology due to their widespread prevalence, diversity of clinical course and frequent adverse outcomes. In recent years, many countries of the world, including Russia, have noted an increase in the proportion of hemocontact hepatitis. St. Petersburg is one of the regions with the highest level of registration of HBV and HCV. The incidence of HCV here is 3.5 times higher than the average for Russia, and has even exceeded the incidence of HBV, which was stopped by the introduction of mass vaccination . High infection with the hepatitis B virus persists in families with patients with chronic forms, and here powerful, long-term foci of infection with a slowly developing epidemic process, which involves new generations , are often formed. The incidence of HCV in children is lower than in adults, but it is necessary to emphasize the alarming situation developing in the adolescent group, where there is a clear increase in infection associated with the spread of intravenous drug addiction.